2016
DOI: 10.1021/acscatal.6b02524
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Mediated Increase in Methanol Production from Photoelectrochemical Cells and CO2

Abstract: While success has been shown in utilizing photocatalytic systems to reduce CO2 in water, most of these studies have yielded formic acid as the major product with trace amounts of formaldehyde or methanol. One reason for this is the strong equilibrium of formaldehyde toward the hydrate methanediol. To increase methanol yields from CO2, we show here the combined use of the biological catalyst alcohol dehydrogenase (ADH) from Saccharomyces cerevisiae with CO2 reduction products obtained from photoelectrochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…According to our results, methanol was not synthesized at all in the absence of the enzymes, Rh complex M , or NAD + , which indicates methanol was generated only through the three‐enzyme cascade reactions. We noted that a small amount of formate (0.15 m m ) was formed with M in the absence of enzymes and NAD + after incubation for 6 h, thus indicating that CO 2 can be partially reduced to formate by M, which was used for the generation of formate and coupled with a subsequent enzymatic reaction in recent studies . However, the amount of formate (2.03 m m ) produced with CcFDH in the NADH‐regenerating PEC system was less than 10 % (see Figure S21).…”
Section: Methodsmentioning
confidence: 99%
“…According to our results, methanol was not synthesized at all in the absence of the enzymes, Rh complex M , or NAD + , which indicates methanol was generated only through the three‐enzyme cascade reactions. We noted that a small amount of formate (0.15 m m ) was formed with M in the absence of enzymes and NAD + after incubation for 6 h, thus indicating that CO 2 can be partially reduced to formate by M, which was used for the generation of formate and coupled with a subsequent enzymatic reaction in recent studies . However, the amount of formate (2.03 m m ) produced with CcFDH in the NADH‐regenerating PEC system was less than 10 % (see Figure S21).…”
Section: Methodsmentioning
confidence: 99%
“…Ullah et al demonstrated that Ir/Ru oxide could efficiently convert of CO 2 into different valuable organic molecules (ethanol as the major product; methanol, acetone and acetaldehyde as the minor products in the liquid phase) . It should be noted that photo‐assisted electroreduction of CO 2 can also selectively generate alcohols through the aid of diversified photocathodes …”
Section: Product Selectivity In Electrocatalytic Co2 Reductionmentioning
confidence: 99%
“…For testing the activity of each semiconductor nanocrystal, nanomolar solutions of either TiO 2 , CdS, or Au@CdS were mixed with an excess of ascorbic acid (90 × 10 −3 m ) and Rh*Cp(bpy) 2 (H 2 O) 2 (0.32 × 10 −3 m ) in phosphate buffer (pH 7) and degassed first for 1 h with Ar followed by a 1 h purge with CO 2 . The sealed solutions were next photoirradiated using a solar simulator (1 sun) for 11 h after which the products formed were characterized by 1 H NMR . As shown in Figure A, TiO 2 nanoparticles conjugated either with amine‐(PEG) 6 ‐azide or DNA showed as expected, little to no ability to reduce CO 2 to any measurable degree.…”
Section: Resultsmentioning
confidence: 76%
“…While formate and methanol can be directly observed in 1 H NMR spectra, the rapid equilibrium of formaldehyde with its hydrate form methanediol complicates formaldehyde quantification. To overcome this, we recently showed that the enzyme alcohol dehydrogenase (ADH) can reduce ultralow levels of formaldehyde to methanol, despite the large equilibrium shift toward methanediol, without any back reactivity . Therefore, after running a CO 2 photoreduction overnight, ADH can be added next in the dark to reduce any formaldehyde present to methanol.…”
Section: Resultsmentioning
confidence: 99%